Transethosome-based topical administration systems with enhanced penetration and dual actions for treating EGFR-overexpressed cutaneous squamous cell carcinoma - Wang, Wenyan (2024)
Epidermal growth factor receptor (EGFR)-overexpressing cutaneous squamous cell carcinoma (CSCC) necessitates more effective therapies due to its elevated metastasis risk compared to the conventional CSCC. While photodynamic therapy (PDT) is a promising way to treat CSCC, effectively administering photosensitizers to reach deeper skin malignancies remains a challenge. Herein, BE-TEL is reported, a transethosome formulation designed to enhance skin and cutaneous tumor permeability, for targeted treatment of EGFR-overexpressed CSCC. The formulation is co-loaded with Erlotinib (Erb), a hydrophobic EGFR inhibitor, and BODIPY (BPY), a photosensitizer. Upon skin penetration and subsequent exposure to 660 nm light, BE-TEL induces tumor cell apoptosis by reactive oxygen species (ROS) generation and EGFR pathway inhibition. ROS and Erb-induced metabolic oxidative stress by upregulating the expression of NADPH oxidase 4 (NOX4) can enhance immunogenic cell death (ICD) and promote dendritic cell maturation for tumor-specific immune response. Furthermore, the EGFR downregulation further mitigated the risk of metastasis and recurrence. In conclusion, BE-TEL's superior penetration ability together with its combined PDT and EGFR targeted approach paves the way for an efficient strategy against EGFR-overexpressed CSCC.